2020
DOI: 10.1021/acs.inorgchem.9b03393
|View full text |Cite
|
Sign up to set email alerts
|

Selective Lanthanide Sensing with Gold Nanoparticles and Hydroxypyridinone Chelators

Abstract: The octadentate hydroxypyridinone chelator 3,4,3-LI(1,2-HOPO) is a promising therapeutic agent because of its high affinity for f-block elements and noncytotoxicity at medical dosages. The interaction between 3,4,3-LI(1,2-HOPO) and other biomedically relevant metals such as gold, however, has not been explored. Gold nanoparticles functionalized with chelators have demonstrated great potential in theranostics, yet thus far, no protocol that combines 3,4,3-LI(1,2-HOPO) and colloidal gold has been developed. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Among luminescent nanomaterials, photoluminescent carbon dots (CDs) have emerged as important materials in sensing and cell imaging [23,24] since the high surface charge of CDs results from the nature of the hydrophilic exterior layer and is predominantly constituted by chelating anions. This is the reason for its high affinity to counter-ions, including metal ions [25,26]. This is the reason for using CDs as effective optical sensors [27][28][29], although the sensitivity of CDs to any changes in their counter-ion environment restricts their applicability in accurate intracellular thermal sensing [30].…”
Section: Introductionmentioning
confidence: 99%
“…Among luminescent nanomaterials, photoluminescent carbon dots (CDs) have emerged as important materials in sensing and cell imaging [23,24] since the high surface charge of CDs results from the nature of the hydrophilic exterior layer and is predominantly constituted by chelating anions. This is the reason for its high affinity to counter-ions, including metal ions [25,26]. This is the reason for using CDs as effective optical sensors [27][28][29], although the sensitivity of CDs to any changes in their counter-ion environment restricts their applicability in accurate intracellular thermal sensing [30].…”
Section: Introductionmentioning
confidence: 99%
“…17 In order to overcome the limitations of DTPA salts as decorporation agents, the octadentate hydroxypyridinonebased chelator 3,4,3-LI(1,2-HOPO) was developed. 18 This synthetic chelating molecule shows high binding affinity for actinides and lanthanides, 19,20 selectivity for f-block elements over biologically-relevant cations, 21,22 formation of excretable complexes with these elements, 23 and biocompatibility at therapeutic dosages. 23 In vivo studies have demonstrated the superior decorporation performance of 3,4,3-LI(1,2-HOPO) for multiple elements, including U(VI), Np(V), and Pu(IV), when compared to DTPA and other chelating agents.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of lanthanides in industrial waste by novel colorimetric assay was achieved by inhibition of gold nanoparticle selective aggregation by LI(1,2-HOPO) was described. [15] The starting elements of lanthanide series, e. g., lanthanum has eight coordination number, the terminal lanthanides such as Lu has nine, whereas the midrange lanthanides like Gd have equilibrium coordination between eight and nine coordination number. The first ligand developed by Raymond et.…”
Section: Introductionmentioning
confidence: 99%